On the Stability of Pt‐Based Catalysts in HBr/Br2 Solution. Issue 7 (11th June 2021) - Liu, Qiang; Meissel, Hubert; Sadykov, Ilia; Jones, Simon; Van Dijk, Nick; Rzepka, Przemyslaw; Artiglia, Luca; Ranocchiari, Marco; van Bokhoven, Jeroen A.
Abstract: Stability studies on supported metal nanoparticles are essential for gaining insight into the design and optimization of high‐performance materials. In this work, the dissolutions of Pt‐based catalysts in HBr/Br2 mixture of various concentration regimes were studied and correlated with material structural properties. The dissolution of metal nanoparticles was enhanced by adding Br2 to the HBr solution. Comparing with commercial Pt/C catalyst, the well‐alloyed PtIr/C catalyst was observed to exhibit high resistance towards dissolution. In addition, regulating the accessibility of the metal sites to dissolution‐inducing species contributed to the marked stability of the nanoparticles in HBr/Br2 solutions, as shown for the surface‐modified PtIr/C catalysts with organic diamine molecules. Abstract :